1993
DOI: 10.1111/j.1751-1097.1993.tb04932.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arctic Ozone Depletion and Snow on Uv Exposure in Finland

Abstract: The increase in the UV exposure of the Finnish population associated with the combined effects of ozone depletion and snow reflection was studied with the aid of theoretical calculations based on Green's clear sky UV model. A simple formula was utilized to transform horizontal irradiances to vertical irradiances averaged over 360 degrees azimuth angle. The model was verified with spectral and broadband measurements. The difference between the theoretical and measured UV radiation falling to horizontal surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…In addition, there is a tendency towards more rapid depletion of the ozone layer over Scandinavia than over most other geographical regions at corresponding latitudes. In contrast to the antarctic ozone hole, which occurs regularly both on a spatial and a temporal scale (Hofmann et al 1992, Davidson & van der Heijden 2000, the arctic ozone hole seems to occur irregularly (Stamnes et al 1988, Jokela et al 1993). The radiation levels within both the visible and the UV bands decrease with increasing latitude due to the increase in the solar zenith angle.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, there is a tendency towards more rapid depletion of the ozone layer over Scandinavia than over most other geographical regions at corresponding latitudes. In contrast to the antarctic ozone hole, which occurs regularly both on a spatial and a temporal scale (Hofmann et al 1992, Davidson & van der Heijden 2000, the arctic ozone hole seems to occur irregularly (Stamnes et al 1988, Jokela et al 1993). The radiation levels within both the visible and the UV bands decrease with increasing latitude due to the increase in the solar zenith angle.…”
mentioning
confidence: 88%
“…Mar Ecol Prog Ser 305: 2005 total ozone has been observed at middle and high latitudes in the Northern Hemisphere during the last decades (Stolarski et al 1992, Jokela et al 1993, Varotsos et al 1998, Dahlback 2002. According to Austin et al (1992), Bjørn et al (1998) and Hessen (2002), this tendency is expected to continue in the 21st century.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Stratospheric ozone depletion is not only reported over Antarctica (Solomon 1999;Staehelin et al 2001) but also over the Arctic (Jokela et al 1993;Mu¨ller et al 1997;Rex et al 1997Rex et al , 2002, which leads to enhanced levels of Ultraviolet-B radiation (UVBR) at the earth's surface. In aquatic ecosystems, reflection and attenuation within the water body reduces irradiance levels and alters spectral composition.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of UV radiation levels in spring in the Arctic can be seen from Jokela et al (1993), who found that on a vertical surface noon-time UV irradiances were higher at the end of April than at any other time of the year in northern Finland. The amount of UV reaching a vertical surface has important biological implications, particularly for the eye (ACIA, 2004) and for the skin of people standing up or sitting down.…”
Section: Introductionmentioning
confidence: 96%